2021
DOI: 10.1186/s13104-021-05454-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender and socioeconomic disparities in reasons for not smoking cigarettes among Danish adolescents

Abstract: Objective To examine gender and socioeconomic differences in adolescents’ reasons for not smoking cigarettes using self-reported data from Danish 14-year-olds (N = 1,559) collected in 2018. χ2-tests were used to assess whether the proportion of students who rated 12 statements as important reasons for not smoking cigarettes differed according to gender and family occupational social class (OSC). Results More girls than boys stated that thinking the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Some studies have already reported that drinking behaviors were higher in male students [ 2 , 14 ]. This study found evidence consistent with this, possibly because female students had more positive attitudes than male students toward the early prevention of drinking or smoking [ 15 ]. However, in some recent studies, there has been little gender difference in drinking and smoking problems [ 16 ].…”
Section: Discussionsupporting
confidence: 69%
“…Some studies have already reported that drinking behaviors were higher in male students [ 2 , 14 ]. This study found evidence consistent with this, possibly because female students had more positive attitudes than male students toward the early prevention of drinking or smoking [ 15 ]. However, in some recent studies, there has been little gender difference in drinking and smoking problems [ 16 ].…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, in a recent study among students enrolled in the X:IT II intervention, students reported that knowing smoking is dangerous and not wanting to be addicted to smoking were the top reasons for not smoking cigarettes. These findings indicate a high awareness of the health-damaging effects of cigarette smoking ( 56 ). However, we do not have knowledge about students' reasoning toward using or not using ATPs.…”
Section: Discussionmentioning
confidence: 75%
“…35 Gender also affects the adoption of preventive smoking initiatives. 36 Accordingly, no supporting evidence has been reported for the effectiveness of gendernonspecific antismoking programs on girls. 37 Given the factors that motivate girls to smoke or quit smoking, researchers recommend gender-specific interventions to be more effective in girls.…”
Section: Discussionmentioning
confidence: 99%